The role of pastoral systems in the creation and maintenance of nature’s contribution to people in Spain - Dean G.; López-i-Gelats F.; Francioni M.; D'Ottavio P.; Rivera-Ferre M.G. (Pastoralism and sustainable development: proceedings, 2021)
Pastoral systems in Spain have been consistently overrepresented in systematic reviews of pastoral and agroecological systems at both global and regional scales. These pastoral systems have been studied extensively through the Ecosystem Service lens, but an examination of Spanish pastoral systems using the Nature’s Contribution to People framework was missing from the literature. The Nature’s Contribution to People framework builds on the Ecosystem Services framework and aims to be more inclusive of social sciences. We hypothesise that the Nature’s Contribution to People framework is well suited to the analysis of pastoral systems as socio ecological systems where human-nature relationships are inherently linked and only decoupled for analytical purposes. In this article, a qualitative comparative analysis was conducted to explore trends throughout the literature on Spanish pastoral systems. Our results displayed that pastoral systems in Spain are regularly studied in terms of only a few dominant Nature’s Contribution to People with Habitat creation and maintenance, Food and Feed and Supporting identities representing 52% of the Nature’s Contribution to People in this analysis and Habitat creation and maintenance being the most common Nature’s Contribution to People in the analysis. These results emphasise the importance of pastoral systems beyond food production.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)